Cybernetics, Anarchism and Self-organisation. - Duda, John (Anarchist Studies, 2013)
The revival and reinvention of anarchist theory in the second half of the twentieth century shared the conceptual stage with the advent of cybernetics. Through a consideration of the works (among others) of Sam Dolgoff, John McEwan, Grey Walter, Paul Goodman and Gregory Bateson, I highlight a few key moments in which the new scientific concepts of systems, circular causality, and self-organisation found their way into anti-authoritarian theory. By untangling the multiple strands of this complicated encounter between anarchism and twentieth-century science, we can better understand the genealogy of contemporary notions around self-organisation, networks and horizontalism, avoid some of the pitfalls encountered by an earlier generation, and find inspiration in some of the avenues afforded by this intersection which are yet to be fully explored.